2022
DOI: 10.3389/fped.2022.936944
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improving the Transition of Patients With Congenital Adrenal Hyperplasia From Pediatrics to Adult Healthcare in Japan

Abstract: The transition of patients with childhood-onset chronic diseases from pediatric to adult healthcare systems has recently received significant attention. Since 2013, the Japan Pediatric Society developed working groups to formulate guidelines for transition of patients with childhood-onset chronic diseases from pediatric to their disease specialty. Herein, we report on the activities of the Japan Society of Pediatric Endocrinology (JSPE) and the current status of transition medicine for 21-hydroxylase deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Implementation of a successful transition in young patients with chronic diseases is crucial to decrease mortality, prevent disease related comorbidities and improve quality of life [7,8]. Studies have shown that up to 50 % of patients with CAH are lost to follow-up leaving paediatric endocrine care, coinciding with a peak of hospital admissions due to manifestation of adrenal crisis (AC) in the second decade of life [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of a successful transition in young patients with chronic diseases is crucial to decrease mortality, prevent disease related comorbidities and improve quality of life [7,8]. Studies have shown that up to 50 % of patients with CAH are lost to follow-up leaving paediatric endocrine care, coinciding with a peak of hospital admissions due to manifestation of adrenal crisis (AC) in the second decade of life [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%